ANALISIS KINERJA KEUANGAN DAERAH PADA SATUAN KERJA PERANGKAT DAERAH PENGHASIL PENDAPATAN ASLI DAERAH DI LINGKUNGAN PEMERINTAH KOTA PALU - Saleh, Hazni (Katalogis, 2016)
The aim of this research is to determine and analyze the growth of actual revenues, effectiveness, activity ratio and contribution of locally generated revenues on each regional revenues-producing government institution in Palu City. Te research is descriptive and its sample consist of 13 regional government unit that are selected through census or non-probability sampling. Tool of analysis used are locally generated revenues growth ratio, locally generated revenues effectiveness ratio, activity ratio with ratio of harmony and tax and contribution analysis of taxes and levies. The resultshows that 1) The growth of loccaly generated revenues is generally fluctuated and there are three local governance unit show negative growth; 2) managerial effectiveness of locally generated revenues is quite effective, and there are three local governance unit showed poor and ieffective performance; 3) spending aspect identifies four local governance units with indirect expenditure greater than direct expenditure; 4) contribution aspect indicates that the majority of revenues in the local government units has less contribution to the locally generated revenues, only two institutions perform good criteria.